Bread Making and Consumption Habits in the Gluten-free Diet - Csapóné Riskó, Tünde; Péntek, Ádám (International Journal of Engineering and Management Sciences, 2018)
Celiac disease is a genetic autoimmune disorder characterized by sensitivity to gluten. Gluten is a protein found in many grain products (wheat, rye, barley and oat). When a person with celiac disease consumes gluten, his/her immune system perceives the gluten to be a harmful substance and reacts negatively. The only treatment for people with celiac disease is lifelong adherence to a gluten-free diet. Bread is a basic and frequently consumed food made from basically gluten-containing grains. Bread plays essential role in the Hungarian dining habits, thus bread consumption in the gluten-free diet is a challenging question. The aim of our empirical research was to investigate the gluten-free bread making and consumption habits of people following a gluten-free diet.